Implementasi Google Cloud Messaging pada Sales Mobile Application - Christine Dewi; Stephen Aprius Sutresno (Universitas Atma Jaya Yogyakarta, 2016)
Abstract. Sales forces are fundamental to determine the smooth process on the marketing firm engaged in sales .One of the companies in the Magelang engaged in sales is PT. Armada Internasional Motor. The car sales process in PT. Armada Internasional Motor still uses manual system. The use of the manual system needs a long time to process car sales to customers. Documents of vehicle order must be approved by several parties by providing signatures on the document. Therefore a new system is needed to solve the problem by building a sales application. The application is built by means of Location Based Service technology useful to help register the location and Google Cloud Messaging as a provider of the information from the server to clients. This research produces the application of a sales system based on mobile android platform that has already integrated various parties and can provide facilities to sales.Keywords: Sales, Android, Location Based Service, Google Cloud Messaging.Abstrak. Karyawan yang memiliki posisi sebagai sales merupakan bagian penting dalam menentukan lancarnya alur proses pemasaran pada perusahaan yang bergerak dalam bidang penjualan. Sales di PT. Armada Internasional Motor masih menggunakan sistem manual dalam penjualan mobil kepada pelanggan. Penggunaan sistem yang manual tersebut membuat sales membutuhkan waktu yang lama untuk melakukan setiap penjualan mobil kepada pelanggan. Untuk itu dibutuhkan sistem baru yang dapat mengatasi masalah tersebut dengan membangun sebuah aplikasi sales. Aplikasi yang dibangun dengan menggunakan teknologi Location Based Service yang berguna membantu pencatatan lokasi dan menggunakan teknologi Google Cloud Messaging yang berguna sebagai pemberi informasi dari server kepada client. Penelitian ini menghasilkan aplikasi sistem sales berbasis mobile pada platform Android yang sudah terintegrasi baik dengan berbagai pihak dan dapat memberikan kemudahan kepada sales.Kata Kunci: Sales, Android, Location Based Service, Google Cloud Messaging.